Decohesion Kinetics of PEDOT:PSS Conducting Polymer Films. (17th October 2013) - Dupont, Stephanie R.; Novoa, Fernando; Voroshazi, Eszter; Dauskardt, Reinhold H.
<x xml:space="preserve">Abstract</x> The highly conductive polymer PEDOT:PSS is a widely used hole transport layer and transparent electrode in organic electronic devices. To date, the mechanical and fracture properties of this conductive polymer layer are not well understood. Notably, the decohesion rate of the PEDOT:PSS layer and its sensitivity to moist environments has not been reported, which is central in determining the lifetimes of organic electronic devices. Here, it is demonstrated that the decohesion rate is highly sensitive to the ambient moisture content, temperature, and mechanical stress. The kinetic mechanisms are elucidated using atomistic bond rupture models and the decohesion process is shown to be facilitated by a chemical reaction between water molecules from the environment and strained hydrogen bonds. Hydrogen bonds are the predominant bonding mechanism between individual PEDOT:PSS grains within the layer and cause a significant loss in cohesion when they are broken. Understanding the decohesion kinetics and mechanisms in these films is essential for the mechanical integrity of devices containing PEDOT:PSS layers and yields general guidelines for the design of more reliable organic electronic devices.